An experimental investigation on LM6 AL-SI alloy sand casting to study the correlation between metallurgical properties and solidification rate - Lim, Y. P.; Sulaiman, Shamsuddin; Hamouda, Abdel Magid Salem; Megat Ahmad, Megat Mohamad Hamdan (Universiti Putra Malaysia Press, 2005)
Aluminium-Silicon alloys constitute one of the commercially important classes of alloys. These alloys are extensively used in automotive and aerospace industries. Forged steel parts are being replaced by aluminium alloy castings to save weight and production costs. This usage often requires a homogeneous microstructure with a high quality. The effect of cooling rate on the solidification microstructure and hardness of an aluminium-silicon alloy is investigated. Carbon dioxide molding process is used to produce the test castings of varying section thickness required for the studies. A data logger is utilized to obtain the temperature distribution contour during the process of solidification of this chosen binary alloy. Hardness values are measured and correlated with the microstructures based on the observations made on this research work and the same is precisely presented here. A graph showing the variation in section thickness versus hardness is highlighted in this paper. Solidification rate is calculated for different section thicknesses theoretically and it is well agreed with the results attained for the aluminium silicon alloy. In recent years, many research papers have been published in different journals and transactions regarding solidification process.